A clean method of precipitation vanadium from the vanadium bearing oxalic acid leaching solution. (1st May 2021) - Chen, Xuexin; Zhang, Jie; Yan, Baijun
Highlights: V can be precipitated by hydrothermal decomposition of [V(C2 O4 )3 ] 3− complex ions. The VO2 hydrothermal synthesis method was introduced into V precipitation process. Based on the vanadium precipitation, the VO2 product with 97% purity was obtained. The hydrothermal vanadium precipitation method can achieve a zero emission process. Abstract: To achieve the clean extraction of vanadium from iron vanadate spinel minerals, vanadium has been successfully leached as [V(C2 O4 )3 ] 3− complex by using oxalic acid as a leaching agent in our previous study. However, the precipitation of vanadium from the V-bearing oxalic acid leaching solution has never been reported. Therefore, an environment-friendly hydrothermal precipitation method was applied in vanadium precipitation process in this study. Firstly, vanadium was effectively precipitated from the V-bearing oxalic acid leaching solution by hydrothermal decomposition of [V(C2 O4 )3 ] 3− complex ions at the temperature above 200 °C to obtain a mixture of vanadium oxides. Based on the vanadium precipitation, to further obtain high purity vanadium oxide product, the hydrothermal precipitation of VO2 from the V-bearing oxalic acid leaching solution was investigated. Before the hydrothermal reaction, an excess hydrogen peroxide solution was employed to oxidize the [V(C2 O4 )3 ] 3− complex ions to form VOC2 O4 in advance. Then, the effect of temperature, the quantity of added V2 O5, and reaction time on the VO2 product preparation and vanadium precipitation extent were investigated. Finally, the uniform and well-crystallized VO2 (B) with 97% purity was obtained, and higher than 99% of vanadium precipitation extent was achieved under the optimum precipitation conditions.